'Do to Me According to What Has Gone Out of Your Mouth'*: A Reformation Debate on the Tragedy of Jephthah and his Daughter. Issue 1 (2nd January 2019) - Amos, N. Scott
ABSTRACT: A challenging biblical passage is the narrative of Jephthah and his daughter in the Book of Judges. The consensus of the exegetical tradition is that in fulfillment of a rash vow, Jephthah sacrificed his daughter as a burnt offering. Yet some early Reformation exegetes argued instead that she entered into a life of dedication to the Lord. They argued on the basis of the grammar of Jephthah's vow, a point which they found in one strand of rabbinical tradition. However, there developed a counter-argument reaffirming the patristic and medieval consensus, and that appealed to an alternative rabbinical tradition. The present essay will examine the competing arguments found in Protestant commentaries published between c. 1530 and c. 1650. In the end, the patristic and medieval consensus prevailed, and the alternative reading was rejected; but both sides agreed that the one noble character in this tale was the nameless daughter of Jephthah.